Viejos estereotipos y nuevos discursos: la visión de Galicia y de los gallegos en una fracción de la élite galaicoporteña a mediados de la década de 1940 - FARÍAS, Ruy (Madrygal. Revista de Estudios Gallegos, 2010)
At the beginning of the XX Century, the intellectual elite of the Galician community in Buenos Aires had created a discourse in opposition to the negative image held by the Argentinean society with regard to those born in Galicia. This paper analyses the continuities and disruptions in that discourse around the ‘40s.